BIMBINGAN KELOMPOK MELALUI TEKNIK DISKUSI UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMA KELAS X IPA - Putri Alawiyah; Heris Hendriana; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
Self-confidence is a positive attitude and behavior of an individual that raises his ability to cultivate and develop a positive assesment, both toward himself and the environment and the situation he is facing. BK teacher and student responses to group guidance service with discussion techniques on student when implementing group guidance service with discussion techniques on the self-confidence of class X / IPA students at SMAN 1 Cipongkor. Qualitative descriptive research methods were collected trough observation, interviews and questinnaires. The scenario steps and their implementation are also in group guidance service with discussion techniques including group formation seen from the students self-confidence problem that have been reviewed by the BK teacher and the results of the AKPD given by the BK teacher, Providing material through video media to stimulate initial confidence for participants. Studen, share opinions about the material provided, conclude, and evaluate the implementation of services. The response of students in self-confidence during the implementation of group guidance services with discussion techniques. Keywords:   Self Confidence, Group Guidance, Discussion Techniques